TELA'AH ATAS PENAFSIRAN BUYA HAMKA DALAM TAFSIR AL-AZHAR TENTANG KEADILAN SOSIAL - Agustina Damanik; Santi Marito (Yayasan Baitul Hikmah al-Zain, 2024)
Social justice is the basis of statehood in Indonesia, but its presence in the joints of social life is far from a materialized word. In this case, many people argue that social justice is a very expensive and rare thing to obtain. In Islam, justice is very important, even in the Qur'an the word adil is mentioned 78 times using 3 kinds of words namely al-'Adl, al-Qisth, and al-Mizan. This research will focus on Buya Hamka's definition of social justice along with the characteristics of justice. The approach used in this study is to use a qualitative approach with a type of literature research. The result of this study on the definition of social justice in the Qur'an according to Hamka is true and balanced to all beings, telling the truth, always defending, and fighting for social benefit. As for the characteristics of Hamka's interpretation of social justice in the Qur'an, it tends to emphasize on noble ethics (morals) and apply firmly in upholding a truth, applying balance to anyone without the influence of sentiment other things. In interpreting these verses, Hamka uses the interpretation of bi ar-ra'yi. This proves, too, that we can judge fairly in society through our minds as well as our consciences